Design and additive manufacturing of a lightweight aerospace electric actuator [version 2; peer review: 1 approved, 2 approved with reservations] - Ekain San José; Sergio Montes; Borja Prieto; Borja Lizarribar Carrillo; Javier García Goikoetxea; Miguel Martínez-Iturralde (Open Research Europe)
Background The ambitious electrification targets set for the aeronautical sector are leading to a thorough research into improving the performance of different electromechanical components. In this regard, Additive Manufacturing is gaining strength due to the positive physical properties of the processed parts and the freedom in manufacturable geometries. Methods Thus, this article presents the design of an electric actuator for an aerospace active sidestick in which Additive Manufacturing is used with the aim of minimising the mass and power consumption of the device. The electromagnetic design of the actuator is detailed, considering 8 different permanent magnet machine topologies, and a mechanical design applying Topology Optimisation to reduce the overall mass of the component is carried out. Results Three prototypes involving the rotor, the stator and the casing are manufactured via Laser Powder Bed Fusion in stainless steel and Permendur (Fe49Co49V2) and the corresponding actuators are experimentally tested, showing a great agreement between tests and simulations and excellent repeatability in the electromagnetic behaviour of the prototypes. Conclusions The research results highlight the great potential of Additive Manufacturing to manufacture functional electrical machine components.